Depressive symptoms among the oldest-old in China: a study on rural-urban differences - Chaoqun Hu; Qinqin Jiang; Yuan Yuan; Bing Hou; Zhe Zhao; Yijun Liu; Jinhai Sun; Lei Yuan (BMC Public Health)
Abstract Background In China, In China, depression among the oldest-old (aged 80 + years) is a major public health issue. As the gap in development between urban and rural China widens, the aim of this study was to demonstrated whether there are disparities in the incidence of depressive symptoms between the urban and rural oldest-old (aged 80+) in China and to quantify the contribution of relevant influencing factors. Methods The study evaluated data on 5,116 oldest adults (female, 55.88%; male, 44.12%) from the 2018 Chinese Longitudinal Healthy Longevity Survey. A chi-square test analyzed the distribution characteristics of related indicators among the oldest-old adults in the two areas. Multiple linear regression was applied to exploring the influencing factors of depressive symptoms in the oldest-old (aged 80+) adults in different regions. The Blinder-Oaxaca decomposition method quantified the four categories of influencing factors (demographic characteristics, sociological characteristics, personal lifestyle, personal lifestyle) of the differences in depressive symptoms and estimated their contributions among urban and rural oldest-old (aged 80+) adults. Results 14.60% of oldest-old (aged 80+) adults reported having depressed symptoms, with rural oldest-old (aged 80+) adults reporting more of these symptoms (15.70%) than urban oldest-old (aged 80+) adults (12.25%). In urban areas, age (90-99: β = -0.583, 95%CI = -1.008 to -0.158), annual income (rich: β = -0.699, 95%CI = -1.368 to -0.029), smoking (yes: β = -0.752, 95%CI = -1.376 to -0.127), exercise (yes: β = -1.447, 95%CI = -1.828 to -1.065), self-rated health status (good: β = -2.994, 95% CI = -3.362 to -2.625) were protective factors against depressive symptoms, and married status (other: β = 1.222, 95%CI = 0.564 to 1.880) were risk factors. In rural areas, education level (1-6: β = -0.374, 95%CI =  -0.686 to -0.062), annual income (poor: β = -0.374, 95%CI = -0.721 to -0.026; rich: β = -0.781, 95%CI = -1.115 to -0.447), exercise (yes: β = -0.844, 95%CI = -1.143 to -0.545) and SRH status (good: β = -3.023, 95%CI = -3.274 to -2.772) were protective factors, whereas body mass index (BMI) (< 18.5: β = 0.532, 95%CI = 0.221 to 0.842) and married status (widowed: β = 0.630, 95%CI = 0.283 to 0.978) were risk factors. The Blinder-Oaxaca decomposition showed that 90.47% of the factors, such as age (90-99, 1.90%), living status (living in an institution, -12.35%), annual income (rich, 42.69%), smoking (yes, -5.56%), exercise (yes, 37.45%), and SRH (good, 19.09%) could significantly explain the depressive symptoms differences between the two populations (p < 0.05). Conclusions The oldest-old (aged 80+) adults in rural areas had a higher prevalence of depressive symptoms than that in urban areas, mostly attributed to variations in income, marital status, physical activity, and health status. These findings can help government agencies design targeted and precise intervention strategies (e.g., health education, improving medical security, and providing sports venues and equipment) to improve mental health and lower the risk of depression among the oldest population.